Tingkat Pengetahuan Swamedikasi Terhadap Penanganan Penyakit Skabies (Sarcopies scabiei) di Pondok Pesantren Se-Kota Singkawang - Apriliyanti, Dea Nur; Kusharyanti, Indri; Purwanti, Nera Umilia (Jurnal Farmasi & Sains Indonesia, 2023)
Data obtained from the Indonesian Ministry of Health, in Indonesia the number of scabies sufferers was 6,915,135 (2.9%) out of a population of 238,452,952 people in 2017. The factor that is believed to be related to the incidence of scabies is a person's level of knowledge. This research method is quantitative with a cross-sectional approach, presenting the level of knowledge with primary data obtained through a questionnaire. The sampling technique used non-probability sampling and obtained a total of 106 respondents who met the inclusion criteria. The results of the study were 48.1% of respondents who got results in the good range, 28.3% sufficient, and 23.6% lacking.